نظرية المصلحة وتطبيقاتها في فتاوى الاقتصادية المعاصرة في هيئة الشرعية الوطنية لمجلس العلماء الإندونيسي: (The Theory of Interest and Its Applications in Contemporary Economic Fatwa in the National Shariah Board of the Indonesian Ulema Council) - Reski Wahyuni Nur, Sri; Abdul Kholiq Hasan, Mohammad; Rosyadi , Imron (AL-WIJDÃN Journal of Islamic Education Studies, 2022)
The study aims to know the position of the rule “wherever there is interest, then God’s judgment” with the National Shariah Board of the Indonesian Ulema Council and its approach to applying the rule in its fatwa, especially those related to Islamic education. The study relied on the analytical descriptive research method, law the method of content analysis or the so-called (content analysis). The study concluded that the position of the rule with the authority is very important in deducing the ruling, and this appears in the authority’s use of this rule in twenty-eight fatwa out of 143 fatwa, and that The approach of the Shariah board in applying the rule is the approach of the righteous predecessors in applying the interest, taking into account the controls of the interest, except in some cases, the board advances the interest, because one of the committee’s approach is the systematic facilitation and reconsideration that depends on them in issuing the fatwa for the benefit of the nation.   Keywords: Maslahat, Fatwa, Rules, Application